(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article authors considered questions of fault of the legal entity in civil law. In difference from fault of the natural person of wine of the legal entity possesses a number of the specific signs characterizing about its special nature. Nevertheless discussions on the matter proceed still. Therefore the authors in this article consider such questions as, whether there is a «psychological» content of fault of the legal entity, whether the legal entity bears responsibility for illegal acts of the employees, in what forms the fault of the legal entity is expressed, in what cases the legal entity bears civil responsibility. Also the authors point to signs of fault of the legal entity and try to give definition to this concept. Key words: subjects of civil law, wine of the legal entity, civil responsibility, harm, causal relationship.